DEPENDENCE OF PROPAGATION LOSS ON ETCHING DEPTH IN AL0.3GA0.7AS/GAAS AL0.3GA0.7AS STRIP-LOADED TYPE WAVE-GUIDES - PARK, KH; BYUN, YT; KIM, Y; KIM, SH; CHOI, SS; CHUNG, Y (SPRINGER, 1995)
Al0.3Ga0.7As/GaAs/Al0.3Ga0.7As strip-loated waveguides were fabricated using a broad-beam electron cyclotron resonance (ECR) ion source. It was found that a very smooth etching profile can be obtained by ECR ion etching and the etching rate of Al0.3Ga0.7As is 70 nm min-1. The propagation losses of strip-loaded type III-V compound semiconductor waveguides with various etching depths were studied by the Fabry-Perot cavity method. It was observed that the reflectance at the cleavage increases slightly with etching depth for TE polarization. The propagation loss is measured as 1.5 dB cm-1 for etching depth of 0.7 mum, less than 1 dB cm-1 for 0.8 mum, and 3.5 dB cm-1 for 1.1 mum.
Keywords: OPTICAL WAVE-GUIDES; GAAS